Islamic Education Revolution in Indonesia: a Review of Harun Nasutions Thoughts - Mubarok, Imam Anas; Mughayyirah, Yuniar (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This research aims to explore Harun Nasutions views on education and then revolutionize education that is related to current developments, especially in Indonesia. The method applied in this study is a literature review, where the author tries to find, organize, and analyze each related reference. The results of this study indicate that Harun Nasution assessed that there was a lag among Muslims in Indonesia. For a long period, Muslims in Indonesia wanted to innovate in education. There are several mistakes that occur in Indonesian Muslim society, where many still rely on traditional learning methods and tend to reject other approaches, so that Muslims in Indonesia are left behind. Many thinkers have tried to create new ideas for Islamic education reform. One of them is Harun Nasution. According to Harun Nasution, there are three approaches that are suitable for reviving Islam. First, the use of rationality in religion. Second, people who have an understanding of Jabariyah also get an understanding of Qadariyah as a comparison and transition. Third, do not reject rationality and God's revelation because both are interconnected. All of this can be applied in various aspects of life experience, especially in the field of education.